PENGARUH LEVERAGE, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERDADAP NILAI PERUSAHAAN - Idha Putri Arastika; Khairunnisa Khairunnisa (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
Maximizing the value of the company and the welfare shareholders is one of the main objectives of the company. Company value is the highest level of investors. The higher the value of the company, the greater the investors who invest and also invest their capital in the company. The aim of this study is to analyze the influence of leverage, profitability, and company growth on the firm value of pharmaceutical sub-sector companies listed in Indonesia Stock Exchange from 2014 to 2018. The financial reports, as the data used in this study, are taken from the official website of Indonesian Stock Exchange (www.idx.co.id). The population in this study refers to sub-sector of pharmaceutical companies listed in Indonesia Stock Exchange from 2014 to 2018. The technique used in this study is purposive sampling. Eight samples of the companies in a five-year period are used. Consequently, there are 40 sample data of pharmaceutical sub-sector companies listed in Indonesia Stock Exchange from 2014 to 2018. The method of panel dataregression analysis is employed by means of software: Eviews 10.0. The analysis simultaneously shows that the leverage, profitability, and the company growth do not significantly influence the firm value. In partial, however, neither leverage nor the company growth influences the firm value, whereas profitability has a positive effect on it.